Spectacular Mexico : design, propaganda, and the 1968 Olympics - Castañeda, Luis M. (A Quadrant book, 2014)
An examination of the relationship between a paradigm-shifting event in global design culture, the 1968 Mexico City Olympics, and the exhibitionary practices of the single-party Mexican state during the mid 20th century. Mexico '68 was the most ambitious of a sequence of official design projects destined to support the claim that, in the aftermath of its revolutionary wars (c1910-1920), a socially unified and prosperous Mexico had effectively arrived to the 'developed' world. This is the first book to explore the intersecting histories of the design interventions aimed to support this claim.